Preparation of strategic development programmes: is participation the right way? - Irena Ðokiæ; Jelena Šišinaèki (European Regional Science Association (ERSA), 2004)
If you want to run a successful regional policy you need to behave similar to the company manager: you need to have vision, mission, strategy and action plans. In Croatia, during the past 13 years, more than 100 official national and regional documents called "strategies", "programmes" or "plans" have been produced. Therefore, it would be reasonable to assume that Croatia has an extensive experience in the production of such documents. Nevertheless, in the last couple of years Croatia has and is still receiving international and financial assistance for the production of development projects. Why? Although many, too many strategic documents were produced, once when the supervisory body adopts such documents, they usually end up in somebody's draw and without any repercussion stay there. Through the international assistance a new, participative methodology in regional development planning was applied with three regional programmes as results. The first section of this paper briefly explains the old practice and distinctive features of the participative methodology. The major part of the paper is focusing on the analysis of the three pilot programmes: Island of Šolta, Town of Virovitica and Town of Samobor. The idea behind these analyses is the critical overview and evaluation of the participative methodology implementation successfulness regional development planning. Although the analysis indicate that there are certain objective as well as subjective obstacles for sound implementation of participative methodology, the three pilot programmes clearly mark the new approach to regional development planning in Croatia. The last section of the paper is providing recommendations for the participation methodology future improvement in regional planning. Key words: regional development, strategic planning, participative methodology
Keywords: 330; regional development; strategic planning; participative methodology